2012
DOI: 10.1002/cta.1844
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a digitally controlled single‐inductor dual‐output (SIDO) buck converter

Abstract: This paper describes design and implementation of a digitally controlled single-inductor dual-output (SIDO) buck converter operating in discontinuous conduction mode. This converter adopts time-multiplexing control in providing two independent output voltages using only an inductor. The design issues of the digital controller are discussed, including static and dynamic characteristics. Implementation of the controller, a modified hybrid digital pulse width modulator and a single look-up table are developed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…(a) Values of K p at which limit cycles are observed as α is varied are shown in red circles. Black line shows bound (7). Parameters as in Figure 10 which has to be satisfied in order to prevent limit cycles on two duty cycle levels, which represents an easing of the requirement on the resolution of the DPWM.…”
Section: Zero-error Bin Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Values of K p at which limit cycles are observed as α is varied are shown in red circles. Black line shows bound (7). Parameters as in Figure 10 which has to be satisfied in order to prevent limit cycles on two duty cycle levels, which represents an easing of the requirement on the resolution of the DPWM.…”
Section: Zero-error Bin Switchingmentioning
confidence: 99%
“…These include the possibilities for greater flexibility and programmability of control laws, a greater insensitivity to parameter variations and low power consumption [2]. Many papers have been published in recent years which deal with implementing digital control schemes in switching power converters, for example [3][4][5][6][7] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in this converter, switches usage is also higher. Finally, from the above literature, it is identified that most of the reported topologies require more than two numbers of switches and input inductors and suffer from higher switching stress 22 …”
Section: Introductionmentioning
confidence: 99%
“…According to the number of inductors, multiple‐output DC‐DC converters can be divided into single‐inductor multiple‐output (SIMO) DC‐DC converters and multiple‐inductor multiple‐output (MIMO) DC‐DC converters 11–15 . Among them, the SIMO DC‐DC converters need only one inductor to realize multiple output power supplies, 16,17 which can become one of the most popular choice in the multiple‐output technology in terms of cost and weight. However, the multiplexing of one inductor at the output ports in the SIMO DC‐DC converters will inevitably lead to strong coupling and nonlinear interaction among the output ports 18 .…”
Section: Introductionmentioning
confidence: 99%